Manajemen Pembelajaran Pendidikan Agama Hindu Berbasis Budaya Lokal (Studi tentang Pembentukan Karakter Siswa pada Pasraman di Bandar Lampung) - Ni Made Indrayani (Pasupati, 2023)
The purpose of this research is to know the planning program, implementation, evaluation, weakness and effort in Hindu religious learning based local culture bali.Data collecting techniques performed through observation, An interview and study documentation with case studies on three pasturages of local culture-based learning programs back in the lamphouse.The problem was reviewed from a theory angle, concept, The foundation of education management and the management of Hindu religious education education. The results of research and data analysis showed the pasraman third in fact planning programs ranging from, the program of instruction and monitoring and evaluation.Planning programs based learning the local culture bali applied is learning through sedhana dharma, dharmatula, dharma discourse, dharmagita, the religious and making upakara facilities.The implementation of effective program of instruction in whose model, a method, tools and source of learning, type the right judgments to support the learning, through the exploration, konfermasi and elaboration. A thorough assessment that includes all aspects of competence that encompass cognitive abilities, psychomotorics, and affective. The pastrade seeks to optimize the execution of unoptimized learning and judgment.